Photoluminescence Characterization of Sm3+-DOPED SrIn2O4 Prepared by a Solution Combustion Method - Pekgozlu, I. (Springer, 2020)
Sm3+-doped SrIn2O4 phosphors were prepared by a solution combustion method. The synthesized phosphors were characterized using powder XRD. The excitation and emission spectra of Sm3+-doped SrIn2O4 materials were analyzed at room temperature. SrIn2O4:Sm3+ phosphor emits 568-578, 606-617, 660, and 720 nm light under ultraviolet excitation of 300 nm. The photoluminescence properties of the synthesized phosphors with different Sm3+-doping concentrations were investigated. The optimum concentration of Sm3+ ion in SrIn2O4 was found to be 0.02 mol.
Keywords: Photoluminescence; Sm3+ Ion; Combustion Synthesis; Srin2o4